Neuromodulatory control of energy reserves in dopaminergic neurons - Camila Pulido; Matthew S. Gentry; Timothy A. Ryan (Proceedings of the National Academy of Sciences, 2025)
The brain is a metabolically vulnerable organ as neurons have both high resting metabolic rates and the need for local rapid conversion of carbon sources to ATP during activity. Midbrain dopamine neurons are thought to be particularly vulnerable to metabolic perturbations, as a subset of these are the first to undergo degeneration in Parkinson’s disease, a neurodegenerative disorder long suspected to be in part driven by deficits in mid-brain bioenergetics. In skeletal muscle, energy homeostasis under varying demands is achieved in part by its ability to rely on glycogen as a fuel store, whose conversion to ATP is under hormonal regulatory control. In neurons, however, the absence of easily observable glycogen granules has cast doubt on whether this fuel store is operational, even though brain neurons express the key regulatory enzymes associated with building or burning glycogen. We show here that in primary mid-brain dopaminergic neurons, glycogen availability is under the control of dopamine autoreceptors, such that dopamine itself provides a signal to store glycogen. We find that when glycogen stores are present, they provide remarkable resilience to dopamine nerve terminal function under extreme hypometabolic conditions, but loss of this dopamine-derived signal, or impairment of access to glycogen, makes them hypersensitive to fuel deprivation. These data show that neurons can use an extracellular cue to regulate local metabolism and suggest that loss of dopamine secretion might make dopamine neurons particularly subject to neurodegeneration driven by metabolic stress.